American born Chinese - Yang, Gene Luen.; Pien, Lark. (New York : Square Fish, 2009)
Alternates three interrelated stories about the problems of young Chinese Americans trying to participate in the popular culture. Presented in comic book format.
Story 1: "All Jin Wing wants is to fit in. When his family moves to a new neighborhood, he suddenly finds that he's the only Chinese American student at the school. Jocki and his bullies constantly pick on him constantly, and he has hardly any friends. Then, to make matters worse, he falls in love with an all-American girl." Story 2: "Born to rule over all the monkeys in the world, the story of the Monkey King is one of the oldest and greatest Chinese fables. Adored by his subjects, master of the arts of kung-fu, he is the most powerful monkey on Earth. But the Monkey King doesn't want to be a monkey. He wants to be hailed as a god ..." Story 3: "Chin-Kee is the ultimate negative Chinese stereotype, and he's ruining his cousin Danny's life. Danny's a basketball player, a popular kid at school, but every year Chin-Kee comes to visit, and every year Danny has to transfer to a new school to escape the shame. This year, though, things quickly go from bad to worse" -- Publisher's description.
"Winner of the Michael L. Printz award"--Cover.
Michael L. Printz Award for Excellence in Young Adult Literature.
Keywords: Graphic novels; Chinese Americans -- Fiction; Identity (Psychology) -- Fiction; Schools -- Fiction; Chinese Americans -- Comic books, strips, etc; Identity (Philosophical concept) -- Comic books, strips, etc; Schools -- Comic books, strips, etc; Cartoons and comics; Printz Medal; Graphic novels; Graphic novels -- United States